2001
DOI: 10.1002/jbt.10001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity and cholestasis in rats induced by the sesquiterpene, 9‐oxo‐10,11‐dehydroageraphorone, isolated from Eupatorium adenophorum

Abstract: Eupatorium adenophorum leaves cause hepatotoxicity and cholestasis in rats. The hepatotoxicant has been characterized as 9-oxo-10,11-dehydroageraphorone (ODA), a cadinene sesquiterpene. Oral administration of ODA, mixed in feed to rats, caused jaundice in 24 h. The liver of the intoxicated animals had focal areas of hepatocellular necrosis, proliferation, and dilation of bile ducts with degenerative changes in the lining epithelium. There was marked increase in the conjugated form of plasma bilirubin and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Previous study indicated that E. adenophorum has the acaricidal activity [68], antitumor activity [9, 10], potential anti-inflammatory and other biological activities [11]. The previous reports showed that purified extracts from E. adenophorum could cause hepatotoxicity of mice and livestock [8, 12–15], especially the 9-oxo-10,11-dehydro-agerophorone which is the main poisonous components of E. adenophorum [16, 17]. Also, when administrated with E. adenophorum freeze-dried leaf powder, the mice were caused hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study indicated that E. adenophorum has the acaricidal activity [68], antitumor activity [9, 10], potential anti-inflammatory and other biological activities [11]. The previous reports showed that purified extracts from E. adenophorum could cause hepatotoxicity of mice and livestock [8, 12–15], especially the 9-oxo-10,11-dehydro-agerophorone which is the main poisonous components of E. adenophorum [16, 17]. Also, when administrated with E. adenophorum freeze-dried leaf powder, the mice were caused hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…adenophorum works as the important toxins of E . adenophorum and had hepatotoxicity [ 6 , 14 ]. These cases suggested that E .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that regular ingestion of E. adenophorum induces chronic pulmonary disease, primarily in Australia, New Zealand, and the Himalayas 2 9 , and the methanolic extract of E. adenophorum leaf samples induces hepatotoxicity in albino mice 10 . Furthermore, feeding rats a diet mixed with purified extracts from E. adenophorum leaf samples causes hepatotoxicity and cholestasis 11 12 , and previous studies have shown that the active Euptox A isolated from E. adenophorum represents an important toxin showing hepatotoxicity 5 13 .…”
mentioning
confidence: 99%